Digital Transformation and Its Influence on Women's Economic Empowerment in Pakistan - Ayesha Javed; Muhammad Zeshan Ashraf; Sumbal Shahbaz (Sustainable Futures)
The evolution of information and communication technology (ICT) has emerged as a transformative force that facilitates women’s economic empowerment, marking it as a relatively new field for investigation. Women's economic participation is vital in achieving economic development, but unequal proliferation of ICT has brought to the forefront the prominent issue of the digital divide across the globe.This study aims to focus on Pakistan, which is enduring accelerated economic change for inclusive economic growth and development. In addition, it is making efforts to increase women's economic participation through digitalization and reduce digital inequalities for women to enhance their financial independence.It encompasses a questionnaire-based survey comprising 110 women participants, which is elaborated through diverse demographics exploring aspects of ownership, usage frequency, and types of digital tools used by the respondents that convey different opinions. 95 percent use smartphones, 74 percent of the women depict extensive digital engagement, and 67 percent use online shopping, but only 37 percent are familiar with financial transactions. Prominent emerging themes are indicated and analyzed, highlighting digitalization tools such as digital literacy, digital learning, digital platforms, digital financial services, and digital entrepreneurship platforms, and their impact on the economic empowerment of Pakistani women.Digital technology is positively linked to skill development, financial inclusion, economic participation, and financial independence. 96 percent of the respondents perceive that it has increased economic opportunities, and 44 percent have participated in online income generation; however, only 38 percent perceive that it has significantly improved their financial independence. This research exercise makes a valuable contribution to the women's empowerment literature by identifying the driving factors as well as the barriers and blockades towards women's economic empowerment in Pakistan.